Evaluating the effectiveness of a preservice teacher technology training module incorporating SQD strategies - Hsu, Yu-Yin; Lin, Chin-Hsi (International Journal of Educational Technology in Higher Education, 2020)
Preparation to use information and communication technology (ICT) is an important component of preservice language teachers’ training, and various existing teacher training models propose a range of strategies for increasing their technology knowledge and technology adoption rates. However, the relative effectiveness of these strategies remains unclear. Based on Tondeur et al.’s ( 2012 ) Synthesis of Qualitative Data model, which delineates the six main teacher preparation strategies (i.e., role modeling, reflection, instructional design, collaboration, authentic experience, and continuous feedback), the present study designed a 4 week training module for preservice language teachers and examined how these training strategies affected 63 participants’ perceived technology knowledge and attitudes toward technology adoption. Among the six training strategies, reflection and instructional design had the highest positive impacts on these preservice teachers’ self-reported knowledge about and attitudes towards using ICT. As well as revealing the relative impacts of each training strategy, the results indicate that our designed training module has considerable potential for application to teacher training in other subjects.